Participação e cultura política no orçamento participativo - Euzineia Carlos (Ciências Sociais Unisinos)
The article discusses social participation in the public budgeting in the municipalities of Vitória and Serra, state of Espírito Santo, Brazil, from 1989 to 2003, and its relation with the local political culture. It analyzes whether and to what extent the relation that is established between participatory practices and the local political culture produces continuation or change in the associative structure and the political career of social actors. In other words, it tries to understand the emerging inter-relation between participation and political culture in the context of a given local associative structure. It also asks about the effects of this inter-relation on the democratizing results of the Participatory Budgeting and on the associative structure of the local actors itself.